Adaption of tribological behavior of a-C:H coatings for application in dry deep drawing - Häfner, Tom; Rothammer, Benedict; Tenner, Jennifer; Krachenfels, Kim; Merklein, Marion; Tremmel, Stephan; Schmidt, Michael; Schmidt, Michael (MATEC Web of Conferences, 2018)
Nowadays the sheet metal forming industry faces challenges regarding efficient usage of resources and sustainability. One strategy to increase the environmental friendliness is to abandon the application of lubricants. The direct contact between tool and workpiece leads to an intensive interaction which increases friction. Especially for deep drawing processes with long sliding distances, this causes distinctive wear. The tool sided application of carbon based coatings is a well-known approach to reduce friction and wear. Former studies have shown a beneficial behavior of hydrogenated amorphous carbon based coatings (a-C:H) to improve the tribological conditions in contact with steel sheets and aluminium alloys under dry conditions. Within this study the coating process and the resulting coating properties will be analyzed. Afterwards mechanical and laser based surface treatment processes prior and after the deposition process will be investigated to reduce the coating roughness. Different roughness values were achieved by varying the surface treatment processes. The laser based finishing enables a reduction of the Spk values by removing single roughness asperities. In order to identify the necessary process parameters for the laser treatment, an analytical model of the material removal was applied. The laser surface treatment achieved similar roughness characteristics compared to mechanical treatment. In this study the tribological behavior of a-C:H coated tools was analyzed under dry conditions within strip drawing tests. The tribological investigations revealed that for dry deep drawing of zinc coated DC04 a broader range of Spk values leads to acceptable tribological conditions whereas for AA5182 a smoother tool surface has to be ensured to prevent adhesion and utilize the full potential of a-C:H coatings.<br
Keywords: Tribology; Surface Modification; Dry Deep Drawing

Analysis of tribological behavior of surface modifications for a dry deep drawing process - Henneberg, Johannes; Rothammer, Benedict; Zhao, Rong; Vorndran, Martin; Tenner, Jennifer; Krachenfels, Kim; Häfner, Tom; Tremmel, Stephan; Schmidt, Michael; Merklein, Marion (Dry Metal Forming Open Access Journal, 2019)
The global trend towards more environment-friendly and sustainable production motivates the development of efficient manufacturing processes. Forming technology has great potential regarding that due to its high material efficiency. Research is necessary to improve the sustainability of established forming processes such as deep drawing. One possibility to improve the environmental friendliness of deep drawing is the realization of lubricant-free processes. This avoids the usage of harmful lubricants. Additionally, it has the potential to shorten process chains by eliminating cleaning steps. However, dry deep drawing is associated with challenges. Due to the lack of a lubricant between tool and workpiece, friction and wear increase. An approach to overcome these challenges is the usage of modified tool surfaces. In this context, the aim of this research is to investigate dry deep drawing operations under application-oriented conditions. Firstly, the cause-effect relationships between the properties and tribological performance for a-C:H and ta-C coating systems as well as laserbased micro-textures are investigated in strip drawing tests using the workpiece materials DC04 and AA5182. Therefore, different amorphous carbon coating approaches for DC04 and AA5182 are evaluated. Beside of coatings, diverse laser micro-texturings are investigated and applied on forming tools. Key parameters are identified, which result in low friction and adhesion. Based on these findings, the different modifications are evaluated. Promising modifications are selected and applied in a novel test rig under application-oriented conditions to analyze their durability. The test rig enables the time- and material-efficient forming of a great number of parts. In this regard, in addition to the occurring process forces, the tool and component topographies are determined at periodic intervals in order to derive the cause-effect relationships between friction, wear and component quality as well as to demonstrate the feasibility of dry deep drawing operations under application-oriented forming conditions.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Modification

Experimental investigation of tool-sided surface modifications for dry deep drawing processes at the tool radii area - Krachenfels, Kim; Rothammer, Benedict; Tremmel, Stephan; Merklein, Marion (Procedia Manufacturing, 2019)
In conventional deep drawing processes lubricants are applied to reduce friction and wear. Demands for increased sustainability, environmental protection and resource efficiency motivate the realization of lubricant-free forming processes. The direct toolworkpiece contact during dry deep drawing leads to changed tribological conditions. Especially in the areas of increased normal and shear stresses, such as the die radius, the dry contact causes an increased risk of wear and damage to the sheet surface. A wellknown approach to face the challenges of dry deep drawing of steel sheets and aluminum alloys is the application of amorphous carbon based coatings on the tool surfaces. Within this study the tribological behavior of conventional and modified tool surfaces at the critical radii area is investigated with a strip bending rotation test. In this test, the friction coefficient is determined based on the relative movement between a rotating test cylinder and a sheet-metal strip bent in a die. For the tribological tests the sheet materials AA6014, AA5182 and zinc coated DC04 are applied. The modification of the tool sided surface was achieved by applying ta-C and a-C:H coatings to the test cylinder. In addition to tests with coated surfaces, tests with uncoated tools are carried out for reference. By analyzing the resulting friction coefficients for the different sheet materials, the suitability of ta-C and a-C:H coatings for dry deep drawing processes is evaluated comparatively. In order to investigate cause-effect relations as well as wear mechanisms, the tool and workpiece surfaces are characterized before and after testing.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings

Influence of laser generated micro textured coated tool surfaces on dry deep drawing processes - Tenner, Jennifer; Häfner, Tom; Rothammer, Benedict; Krachenfels, Kim; Zhao, Rong; Schmidt, Michael; Tremmel, Stephan; Merklein, Marion (Dry Metal Forming Open Access Journal, 2018)
The idea of sustainability and resource conservation promotes the development of energy-efficient and low-emission production processes. A lubricant-free sheet metal forming process is considered as one of these environmentally friendly production technologies. Metal forming processes without conventional lubricants shorten process steps and reduce additional costs, such as removal of residual lubrication from the workpiece after forming. In order to realize such a dry forming process and effectively control the material flow, amorphous carbon coatings were applied to the tool surfaces and a brushing process was carried out as a surface finishing process for roughness adjustment. Laser generated micro features on the surface should make an effective contribution to local friction adaptation. The transferability of strip drawing test to strip bending rotation test was successfully demonstrated by dry and oiled blank reference tests. The first modification of the tool sided surface was achieved by applying ta-C and a-C:H layers. The influence of the coatings on the tribological behaviour was determined in strip drawing tests for DC04 and AA5182. Additional friction adaptation is made possible by the fine and flexible laser based micro texturing of the coated tool surface. Experiments were carried out with different coverage and depth of the laser generated features in order to analyze the tribological influence. Flat and deep features with a degree of coverage of 20 %, 35 % and 50 % are considered in order to analyze the factors influencing their tribological behavior. Compared to ta-C coated references, it can be seen that micro features on the ta-C coated tool surface causes a friction reduction for DC04, independent of the features depth. However, deep laser generated features in particular lead to an increase in friction for AA5182, so that this could potentially lead to a selective local increase in friction in the flange area. For the transferability of the tribological system from the flat application case to a curved tool surface, the basics for laser based texturing of cylinder surfaces are illustrated. The limits of the holographic beam shaping technology used for this are demonstrated.
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Texturing

Influence of varying sheet material properties on dry deep drawing process - Krachenfels, Kim; Rothammer, Benedict; Zhao, Rong; Tremmel, Stephan; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2019)
Deep drawing is one of the most important processes in sheet metal forming. Conventionally, lubricants are used to reduce friction and wear. Demands for increased sustainability, environmental protection and resource efficiency motivate the realization of lubricant-free forming processes. The direct contact between tool and workpiece during dry deep drawing results in changed tribological conditions, which cause an increase in friction and wear. Friction-reducing surface modifications of the tool such as carbon based coatings are being developed for the adaptation of the tribological conditions. The aim of this work is the simulation-based analysis of the stress spectrum for varying sheet properties for the qualification of wear-reducing surface modifications for a wide range of applications. By a simulation model for a rectangular cup, the influence of different batches of steel and aluminum materials with varying friction coefficients and mechanical properties is investigated within the framework of variant simulations. The tribological conditions in the simulation are described on the basis of friction coefficients from the strip drawing test. From the simulation results, the applicability of surface modifications for dry deep drawing is being evaluated depending on the sheet specific properties.<br

Investigation of the tribological performance of a-C:H coating systems by modifying adhesive layer for application in dry deep drawing - Rothammer, Benedict; Zhao, Rong; Krachenfels, Kim; Merklein, Marion; Tremmel, Stephan (International Tribology Conference Sendai 2019, 2019)
Lubricants are essential in conventional deep drawing processes to improve the tribological behavior and product quality. Requirements for increasing sustainability and resource efficiency motivate the realization of lubricant-free deep drawing processes. However, the direct contact between tool and workpiece during dry deep drawing leads to increased adhesive wear and surface damage on the sheet metal. A promising approach to face these challenges due to dry deep drawing is the application of amorphous carbon coating systems on tool surfaces. The roughness peaks on the coating surface caused by deposition have to be kept as low as possible, in order to reduce the risk of abrasive wear caused by interlocking into the ductile metal sheet and thus the initial adhesive wear can be avoided. In this study, the influence of adhesive layer on the topography of a‑C:H functional layer is investigated and its tribological performance verified. The modified deposited a‑C:H coating system exhibits similar adhesion to the substrate as the standard a‑C:H coating system. In addition, it shows a more homogeneous surface topography without formation of droplets. Due to the modified adhesion layer, the Rpk value in as-deposited state is 10 times lower by changing the deposition technique of the chromium adhesive layer. As a result, the extremely low roughness peaks of the coating penetrate only slightly into the rough sheet surface with EDT texturing. The standard and modified a‑C:H coated tool surfaces against two common used aluminum alloys (AA6014, AA5182) are applied for the tribological evaluation by the flat strip drawing test. The analysis of the resulting coefficients of friction shows that the tribological behavior is directly influenced by the roughness. The roughness of the functional layer and thus the tribological behavior can be changed by the application of different adhesive layers. Furthermore, the tool and workpiece surfaces are characterized before and after the test in order to investigate wear mechanisms on tool
Keywords: Tribology; Dry Sheet Metal Forming; Diamond-like Carbon (DLC) Coating; Roughness

Laser based techniques to adapt the tribological conditions in dry deep drawing - Vorndran, Martin; Häfner, Tom; Rothammer, Benedict; Krachenfels, Kim; Merklein, Marion; Tremmel, Stephan; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)
Sheet metal forming is widely used in industry to transform a flat metal sheet to a final shape. However, sheet metal forming requires the use of lubricants to prevent the direct contact between tool and workpiece. These lubricants are often toxic and have to be removed after the forming process. Therefore, the environment and the process chain will profit from the abandonment of lubricants. The use of tool sided coatings is a well-known approach to substitute lubricants and perform dry deep drawing. To achieve satisfying results in deep drawing it is beneficial to tune the tribological conditions. Here, we show laser based techniques to locally adapt the tribological conditions by either reducing the roughness of the surface or by creating structures within the surface. It is e.g. shown that the reduced peak height of coated surfaces can be decreased by a laser process. Furthermore, the resulting tribological conditions are investigated for zinc coated DC04 and AA5162 specimens. In Addition to the tribological behavior the changes of the chemical coating properties are investigated using Raman spectroscopy.<br

Lubricant free forming with tailored tribological conditions - Henneberg, Johannes; Rothammer, Benedict; Zhao, Rong; Vorndran, Martin; Tenner, Jennifer; Krachenfels, Kim; Häfner, Tom; Tremmel, Stephan; Schmidt, Michael; Merklein, Marion (Dry Metal Forming Open Access Journal, 2020)
Changed ecological and economic situations motivate research into environmentally friendly and efficient manufacturing processes. Forming without lubricant has the potential to meet both requirements by avoiding the usage of environmentally harmful lubricants and shortening the process chain by omitting lubricant application and component cleaning. Within the scope of the project, an increase in friction and adhesive wear were identified as major challenges, resulting in failure of components due to cracking. Therefore, this project focused on the investigation of measures to meet these challenges. Amorphous carbon coatings, the reduction of roughness and the application of discrete microtextures were considered as potential measures. Hydrogen-containing amorphous carbon coating systems (a-C:H) fabricated by reactive physical vapor deposition (PVD), plasma-enhanced chemical vapor deposition (PECVD) and PVD/PECVD hybrid techniques, as well as a PVD-generated tetrahedral hydrogen-free amorphous carbon coating (ta-C) were investigated with respect to their properties and tribological performance Three specific profile requirements –a dopant free carbon network, smooth and defect-free surfaces and a high coating adhesion to substrate –are identified as requirements, in order to prolonger the service life of the coated tools. Moreover, to enable the steering of the material flow ultrafast laser based micro texturing for locally tailored tribological conditions were investigated. Thereby two wavelength dependent ablation regimes which differ in ablation mechanism and freedom of form were identified. Using these approaches the friction coefficient could either be reduced by up to 20 % or selectively increased. To improve the efficiency of the process, several beam shaping approaches were evaluated to provide a homogeneous beam profile for uniform modification. By applying ta-C and a-C:H coatings in forming tests, the findings of the laboratory tests were validated and the feasibility of lubricant free deep drawing was proven. In order to benefit from the forming-process-specific advantages, high quantities and therefore high durability of the measures are required. An application-oriented wear test rig has been designed to investigate their durability. By this, it was proven that 3 000 components can be produced from DC04 without wear with both a-C:H and ta-C coatings, and thus increasing tool life by a factor of 15 compared to unmodified tools. Even in the case of wear-critical AA5182, 3 000 parts were produced without wear using ta-C. Within the scope of the project, a fundamental understanding of lubricant free deep drawing processes and measures was created and proof of feasibility in form of a high number of components was achieved.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Surface Modification; Beam Shaping

Nachhaltige Blechumformung durch Trockentiefziehen - Krachenfels, Kim; Tenner, Jennifer; Merklein, Marion (wt Werkstattstechnik - Online, 2018)
Werkstattstechnik online 108 (2018), S. 652-656
LFT Import::2019-07-29 (2328)